Let f(x) = x^3 -2x^2-29x-42. a)Show (x+2) is a factor b)Factorise f(x) completely

a) To show (x+2) is a factor, we want to show f(-2)=0. So (-2)^3-2(-2)^2 -29(-2)-42=-8-8+58-42=0
b) Divide  x^3 -2x^2-29x-42 by x+2 to get x^2-4x-21 which we factorise to get (x+3)(x-7). Hence f(x)=(x+2)(x+3)(x-7)

Related Maths A Level answers

All answers ▸

The curve C has parametric equations x=2cos(t) and y=3cos(2t). Find and expression for dy/dx in terms of t.


Find the turning points of the equation y=4x^3-9x^2+6x?


Given that y = sin(2x)(4x+1)^3, find dy/dx


Why does 'x' need to be in radians to differentiate 'sin x'?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences